Case report: Rapid improvements of anorexia nervosa and probable myalgic encephalomyelitis/chronic fatigue syndrome upon metreleptin treatment during two dosing episodes - Hebebrand, Johannes; Antel, Jochen; von Piechowski, Linda; Kiewert, Cordula; Stüve, Burkhard; Gradl-Dietsch, Gertraud (Frontiers in Psychiatry, 2023)
A comorbidity of anorexia nervosa (AN) and myalgic encephalomyelitis (ME/CSF) is uncommon. A 17 years-old male adolescent with possible onset of ME/CFS after an Epstein Barr Virus infection (EBV) and later onset of AN during a second period of weight loss was twice treated off-label with metreleptin for 15 and 11 days, respectively. As in previous cases, eating disorder specific cognitions and mood improved. Interestingly, fatigue and post-exertional muscle pain (P-EMP) improved, too. We discuss potential mechanisms. Treatment with metreleptin may prove beneficial in AN and in ME/CSF associated with substantial weight loss.